Pembelajaran Materi Ilmu Kalam dalam Mata Pelajaran Aqidah Akhlak untuk Meningkatkan Prestasi Belajar Peserta Didik Kelas XI MIA 1 di MA Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Ajaran 2024/2025: Penelitian - Khotni, M. Darul; Hartati, Suci; Sadiyah, Halimatus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the implementation of Ilmu Kalam material in the Aqidah Akhlak subject and its influence on improving the academic achievement of Grade XI MIA 1 students at MA Hidayatul Mubtadiin Jati Agung, South Lampung, in the 2024/2025 academic year. This research is a descriptive qualitative study using a qualitative approach. Descriptive research aims to systematically present factual and accurate information regarding specific facts and characteristics of a given population. Qualitative research is used to explore natural conditions of the research object, where the researcher serves as the key instrument.The results of the study indicate that the teaching of Ilmu Kalam was carried out in a structured manner and emphasized an active learning approach. Teachers did not only deliver the material verbally but also directly involved students through discussions, question-and-answer sessions, reflections, and the use of digital media. This learning model aligns with the constructivist approach, which encourages students to build understanding through active engagement. Test results showed a significant improvement in student academic performance after the application of contextual and dialogical Ilmu Kalam learning. The success of the learning process was supported by several factors, such as teacher competence, availability of adequate facilities, and a religious school environment. Meanwhile, obstacles such as limited time and complex terminology were addressed through innovative learning strategies and motivational efforts. Overall, the implementation of Ilmu Kalam learning proved to be effective in enhancing students’ cognitive, affective, and spiritual aspects